Assessment of patient satisfaction toward pharmaceutical information services in community pharmacy - Yuniharce Kadang; Arqian Julyansyah (Edukasi Ilmiah Indonesia, 2025)
Pharmaceutical information services (PIS) are vital to pharmacy practice standards that focus on providing patients with accurate and comprehensive drug-related information. This service plays a significant role in enhancing patient compliance and ensuring rational drug use. The present study aims to assess patient satisfaction with pharmaceutical information services at Nur Ichsan Pharmacy, Makassar City. A descriptive research design was applied, using questionnaires as the primary data collection tool. The Likert scale was employed to measure patient satisfaction levels. Sampling was conducted using a quota sampling technique, involving 70 respondents who met the inclusion criteria. Data were analyzed quantitatively and presented as percentage scores. The findings revealed that the overall level of patient satisfaction toward pharmaceutical information services at Nur Ichsan Pharmacy was categorized as satisfied, with an average satisfaction percentage of 76.24%. Among the five service quality dimensions, assurance showed the highest satisfaction level (83.52%), followed by tangible (77.04%), responsiveness (74.66%), empathy (74.28%), and reliability (71.61%). These results indicate that patients were generally satisfied with the service quality, particularly regarding professionalism, safety assurance, and physical facilities. However, improvements are needed in the consistency of information delivery and the written documentation of drug information. Strengthening these aspects can enhance pharmaceutical care quality and promote rational drug use in community pharmacies